THE ROLE OF CORPORATE GOVERNANCE IN LIMITING CREATIVE ACCOUNTING PRACTICES - Ahmad Anwar Saad Al-Hadrawi (Scholar Express Journals, 2024)
This research explored the importance of governance in organizations and how it can limit creative accounting techniques from academics' and specialized accountants' perspectives in Lebanon. The researchers used quantitative data to analyze and evaluate the validity of the research hypotheses statistically. For data collection, a survey questionnaire was created using previous studies and relevant literature, and a random sample of 384 academics and accounting professionals in Lebanon was randomly selected. Out of 384 questionnaires distributed, 347 valid questionnaires were returned, resulting in a 90% response rate. For Statistical analysis, the researcher used the Statistical Package for Social Sciences (SPSS) to verify suggested hypotheses. The researchers found that corporate governance principles, including transparency, disclosure, and stakeholder participation, significantly limit creative accounting practices. The research concluded with recommendations for companies, employers, accountants, and Lebanon's Association of Certified Accountants
Keywords: Cybersecurity; Business; Finance; Corporate governance